2004
DOI: 10.1063/1.1803913
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and ferroelectric properties of sol-gel derived Bi3.15Nd0.85Ti3O12 thin films on Pt∕Ti∕SiO2∕Si(100)

Abstract: Bi 3.15 Nd 0.85 Ti 3 O 12 (BNdT) thin films were deposited on Pt∕Ti∕SiO2∕Si substrates using a sol-gel process. The film annealed at 750°C is composed of grains of 50–100nm in diameter. The fine grains show nearly random orientations. “Micropores” were frequently observed at the junctions of the grains and they are mostly amorphous, while sometimes containing very fine crystalline particles with sizes of only a few nanometers. The BNdT film capacitors with a Pt top electrode showed excellent ferroelectric prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…The value of nonvolatile polarization (P sw −P ns ) of the BNT film decreased by 5.3%. Such high fatigue endurance was better than that observed by Li et al [9] in a sol-gel derived BNT thin film which did not show significant fatigue up to 5×10 9 switching cycles. It is well known that the triple layers of Ti-O octahedron are sandwiched between (Bi 2 O 2 ) 2+ layers in BTO-type perovskite structure.…”
Section: Fatigue Propertiescontrasting
confidence: 53%
See 1 more Smart Citation
“…The value of nonvolatile polarization (P sw −P ns ) of the BNT film decreased by 5.3%. Such high fatigue endurance was better than that observed by Li et al [9] in a sol-gel derived BNT thin film which did not show significant fatigue up to 5×10 9 switching cycles. It is well known that the triple layers of Ti-O octahedron are sandwiched between (Bi 2 O 2 ) 2+ layers in BTO-type perovskite structure.…”
Section: Fatigue Propertiescontrasting
confidence: 53%
“…Recent studies revealed that Bi 3+ ions in Bi 4 Ti 3 O 12 (BTO) could be substituted by trivalent lanthanide ions, such as La 3+ , Nd 3+ , Gd 3+ , Sm 3+ and Pr 3+ , resulting in improvement in the ferroelectric properties. Lanthanide-substituted BTO materials (Bi 4−x Ln x Ti 3 O 12 , BLnTO), such as Bi 4-x La x Ti 3 O 12 (BLT x ) [7] , Bi 4-x Nd x Ti 3 O 12 (BNT x ) [8][9][10] , Bi 3.25 Eu 0.75 Ti 3 O 12 [11] and Bi 4-x Sm x Ti 3 O 12 [12] , are promising lead-free materials for ferroelectric memory devices because of relative high spontaneous polarizations, good endurance to fatigue, and low coercive fields. Of these BLnTO materials, BLT x and BNT x have been receiving great attention.…”
mentioning
confidence: 99%
“…However, its polarization fatigue is a principal drawback for applications [3,4]. On the other hand, BNT is of resistance to polarization fatigue despite its relatively poor ferroelectric and dielectric properties [5,6]. It is therefore of interest to study the feasibilities of effectively combining PZT and BNT, in order to improve the electrical properties of ferroelectric thin films.…”
Section: Introductionmentioning
confidence: 98%
“…A number of studies have been made with the electrical properties of individual Pb(Zr 0.52 Ti 0.48 ) O 3 (PZT) and (Bi 3.15 Nd 0.85 )Ti 3 O 12 (BNT) thin films for these applications [3][4][5][6]. PZT possesses attractive ferroelectric and dielectric properties, which make it a promising candidate.…”
Section: Introductionmentioning
confidence: 99%
“…Rareearth-element-substituted Bi 4 Ti 3 O 12 films are promising due to their fatigue endurance on Pt electrodes [1,2]. Bi 3.25 La 0.75 Ti 3 O 12 and Bi 3.15 Nd 0.85 Ti 3 O 12 (BNdT) films have received attention for their large remanent polarization P r [3][4][5][6][7][8][9][10][11]. Bi 4 Ti 3 O 12 is monoclinic with the space group B1a1 but can be considered pseudo-orthorhombic with a = 0.545 nm, b = 0.541 nm and c = 3.283 nm.…”
Section: Introductionmentioning
confidence: 99%